Adjuvant chemotherapy following stereotactic body radiotherapy for early stage non-small-cell lung cancer is associated with lower overall: A National Cancer Database Analysis. (April 2019) - Foster, Corey C.; Rusthoven, Chad G.; Sher, David J.; Feldman, Lawrence; Pasquinelli, Mary; Spiotto, Michael T.; Koshy, Matthew
Highlights: Early stage non-small-cell lung cancer (NSCLC) often fails distantly post-SBRT. Adjuvant chemotherapy associated with lower overall survival (OS) for T1-3N0 NSCLC. Adjuvant chemotherapy did not associate with OS for T1-3N0 NSCLC ≥ 4 cm. Adjuvant chemotherapy associated with lower OS after propensity-score matching. Other strategies to lower distant failure and improve OS warrant investigation. Abstract: Objectives: Adjuvant chemotherapy is routinely offered post-surgical resection for early stage non-small-cell lung cancer (NSCLC) ≥4 cm; however, its role following definitive stereotactic body radiotherapy (SBRT) has not been well defined. We investigated the association between receipt of adjuvant chemotherapy post-SBRT and overall survival (OS) for patients with T1-T3N0M0 NSCLC in the National Cancer Database (NCDB). Materials and Methods: The NCDB was queried for patients with T1-T3N0M0 NSCLC treated with definitive SBRT from 2004 to 2014. The association between non-randomized receipt of adjuvant chemotherapy and OS was analyzed for all patients ( n = 24, 011) and a propensity-matched cohort ( n = 608) using Kaplan-Meier methods and Cox proportional hazard models. A subset analysis was performed for patients with tumors ≥4 cm ( n = 2, 323). Results: There were 24, 011 patients in the cohort with a median follow-up of 32.5 months. Of these, 322 (1.3%) received adjuvant chemotherapy. Three-year OS was 41.3% with adjuvant chemotherapy compared to 50.6% without adjuvant chemotherapy ( p = 0.001). On multivariate analysis, adjuvant chemotherapy was independently associated with higher overall mortality (hazard ratio:1.22, 95% confidence interval:1.06–1.40, p = 0.005). For tumors ≥4 cm, 3-year OS was 38.2% with adjuvant chemotherapy ( n = 80) compared to 33.0% without adjuvant chemotherapy ( p = 0.81). After propensity-score matching, there was a persistent association between lower OS and adjuvant chemotherapy with those receiving adjuvant chemotherapy ( n = 322) having 3-year OS of 41.3% compared to 60.9% without adjuvant chemotherapy ( p < 0.0001). Conclusion: Adjuvant chemotherapy following definitive SBRT for T1-3N0M0 NSCLC is associated with lower OS and is not associated with a survival benefit for patients with tumors ≥4 cm.